Qualitative and quantitative analysis of formaldehyde in samples of hair straighteners and suitability of the labels - Silvestre, Amanda Letícia Polli [UNESP]; Fagá, Maira; de Almeida-Cincotto, Maria Gabriela José; Chiari-Andréo, Bruna Galdorfini; Formariz, Thalita Pedroni (Editora Cubo, 2020)
Formaldehyde is an active compound, irregularly used in hair products, that has the property of straighten and waterproofing the wires. However, it is highly toxic and can stimulate dermatological hypersensitivity and cancer. In this context it is of fundamental importance the inspection of these products that can be used in safe conditions for the consumer, without formaldehyde in concentrations higher than the allowed. Thus, the aim of this research was the qualitative and quantitative identification formaldehyde in samples of hair straighteners that was obtained by donation in the beauty salons of Araraquara-SP. In addition, the analysis of the packaging labels of the products tested were conducted, following the requirements of the national legislation-RDC 07/2015 which defines the mandatory labeling standards for cosmetic products. A qualitative analysis for formaldehyde identification is based on the formation of a purple colored complex. The quantitative analysis was performed by spectrophotometry. The qualitative and quantitative formaldehyde analysis methods were applied to 13 bottles of hair straighteners. When submitted to qualitative analysis, all samples showed formaldehyde presence. The quantitative analysis demonstrated that the samples identified as B, C, D, E, G, H, I, J and M presented formaldehyde concentration of 3.5 to 14.5%, which is above of the limit recommended by the National Health Surveillance Agency (ANVISA), of 0.2%. In the label analysis, in all samples were found irregularities.
Keywords: Formaldehyde; Hair Straightener; Qualitative Analysis; Quantitative Analysis; Spectrophotometry